A dipole polarizable potential for reduced and doped CeO(2) obtained from first principles. - Burbano, M; Marrocchelli, D; Yildiz, B; Tuller, H; Norberg, S; Hull, S; Madden, P; Watson, G (2011)
In this paper we present the parameterization of a new interionic potential for stoichiometric, reduced and doped CeO(2). We use a dipole polarizable potential (DIPPIM: the dipole polarizable ion model) and optimize its parameters by fitting them to a series of density functional theory calculations. The resulting potential was tested by calculating a series of fundamental properties for CeO(2) and by comparing them against experimental values. The values for all the calculated properties (thermal and chemical expansion coefficients, lattice parameters, oxygen migration energies, local crystalline structure and elastic constants) are within 10-15% of the experimental ones, an accuracy comparable to that of ab initio calculations. This result suggests the use of this new potential for reliably predicting atomic scale properties of CeO(2) in problems where ab initio calculations are not feasible due to their size limitations.